Review of Trimester-Specific Gestational Weight Gain and Childhood Adiposity - Thapa, K (Journal of Nepal Paediatric Society, 2014)
Childhood obesity is a global epidemic and a major public health challenge. There has been increasing evidence that intrauterine exposures, such as alcohol, smoking, and maternal nutritional status, may affect both the long and short term health consequences of the mother and offspring. Childhood adiposity may be affected by the mother’s pre-pregnancy weight and her weight gain during pregnancy. Consequently, interventions may need to start before conception of the child to prevent childhood obesity. In 2009, the Institute of Medicine updated its gestational weight gain recommendations by incorporating rates of gestational weight gain in the second and third trimesters based on the mother’s pre-pregnancy Body Mass Index. There is extensive research on the association between total gestational weight gain and short-term offspring adiposity. However, this review focuses on the association between trimester-specific gestational weight gain and childhood adiposity for singleton pregnancies with respect to the Institute of Medicine’s newly defined weight gain recommendations as very few studies have examined the association between the gestational weight gain during each trimester and childhood adiposity. Identifying the trimester that is most associated with childhood adiposity may help in the development of targeted interventions, guide physician’s nutritional and weight-gain recommendations for child-bearing mothers, and direct future research. DOI: http://dx.doi.org/10.3126/jnps.v34i1.8429 J Nepal Paediatr Soc 2014;34(1):48-53